Stock market manipulation: A comparative analysis of East Asian emerging and developed financial markets - Shah, Syed Qasim; Ismail, Izlin; Shahrin, Aidil Rizal (Growing Science, 2019)
The study investigates the firm’s specific characteristics of manipulated firms in East Asian emerging and developed markets using hand-collected 244 manipulated cases between 2001 and 2017. The empirical analysis is conducted using panel logistic regression to identify which stocks are more likely to be manipulated. Result shows that large and highly liquid firms were more likely to be manipulated in both emerging and developed markets. Additionally, marginal effect shows that firms with high free float and market capitalization had a higher probability of being manipulated in these markets. On the contrary, profitable firms were less likely to be manipulated in both developed and emerging markets. Limited studies have been conducted to empirically identify the characteristics of the manipulated stocks across the developed and emerging markets. The regulator can use these results to identify possible and expected manipulation and to design enforcement rules, accordingly. Further, investors can take into consideration these characteristics of manipulated stocks while designing their portfolio in order to reduce the portfolio risk.